Synthesis, Spectroscopy, and DFT Studies of Molybdenum (0) Complexes Incorporating the (NN'), (NO) & (OO') Chelating Mixed Ligands as quinoxaline-2,3-dione, 8-hydroxyquinoline, and 2,2'-bipyridine - Elshweref, Somiya F.; Ashoor, Salem Eltuhami; Belkhiric, Lotfi; Alfallous, Khalifa A.; Ebrahem, Amina; Ibrahim, Amel Belgasem; Khlifa, Moussa I. (European Journal of Applied Sciences, 2026)
The complexes with the formulas [Mo(bipy)(QX)(CO)2], [Mo(bipy)(8HQ)(CO)2], and [Mo(bipy)(8HQ)(QX)] (where QX = quinoxaline-2,3-dione; 8HQ = 8-hydroxyquinoline; bipy = 2,2-bipyridine) were synthesized in two steps. First, Mo(CO)6 was reacted with bipy, and then the QX ligand or 8HQ was added. Initial characterization, based on elemental and mass analyses, suggested three potential structures denoted as 1–3. In these structures, the QX, 8HQ, and bipy ligands coordinate with the Mo(0) centers through their C=O, ON, and NN functional groups. Infrared (IR) studies clarified the coordination modes of the ligands, particularly in the carbonyl region of the spectrum. Proton Nuclear Magnetic Resonance (1H NMR) studies in DMSO-d6 exhibited patterns corresponding to the cis-(bipy)2, QX, or 8HQ moiety. The electronic spectra of the complexes were characterized by charge-transfer transitions, including Mo(dπ)→ C=O (π*), Mo(dπ)→ ON (P: SP2) 8HQ, and Mo(dπ)→bipy(SP2), reflecting metal-to-ligand charge transfer (MLCT). The structural and vibrational properties, including the energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) for the complexes [Mo(bipy)(QX)(CO)2], [Mo(bipy)(8HQ)(CO)2], and [Mo(bipy)(8HQ)(QX)], were elucidated using Gaussian09 and Amsterdam Density Functional (AMS/ADF) software. This analysis employed parameterized DFT/B3LYP/6-311G* and the B3LYP method with the TZP basis set.